Profil Keterampilan Regulasi Metakognisi Ditinjau dari Strata Angkatan Mahasiswa Pendidikan Biologi - Roisyah Ashshaddiqah Suwandi; Amelia Happy Beauty; Sulis Pujiyanti; Avis Alfara; Fattahu Husna Nurisma; Baskoro Adi Prayitno (Jurnal Pendidikan Biologi, 2019)
This research aims to determine the profile of metacognition regulation skills and determine the differences in metacognition regulation skills of Biology Education students at one of the Universities in Surakarta based on the strata of the class. This research method uses a survey method. The research population was Biology Education students at one of the Universities in Surakarta consisting of 4 classes totaling 240 students. The research sample was obtained by stratified random sampling technique as much as 30% of the population, namely 18 students per class. The research data was obtained through a questionnaire that referred to the Metacognitive Awareness Inventory (MAI) with indicators of Metacognitive Regulations, including Planning, Information Strategy, Monitoring, Coordination Errors, Understanding Strategies, and Evaluation. Analysis of research data was carried out in quantitative descriptive and ANAVA test. The results of the research showed that the profile of metacognition regulation skills in each class averaged 79.51% with a well-developed category. The profile of the 2015 metacognition regulation skills is 77.80% with a category that has developed well, the 2016 class is 82.48% with a category that has developed well, the 2017 class is 79.81% with a well-developed category, and 2018 is 79, 97% with a well developed category. Skill in regulating metacognition of Biology Education students in Surakarta in 2018/2019 has developed well. The 2016 Biology Education students have the highest average metacognition skills with a score of 82.48%. ANAVA test results showed no difference in metacognitive regulation for each class with a significance value of 0.054.